Analysis of Learning Evaluation Results and Follow-up - Rizka, Zakiyah Sabilah; Arbeni, Wawan; Tanjung, Silvi; Bahagia, Sindia Putri; Pratama, Ridho Bagus; Lubis, Wulandari; Adila, Nur Fadiah (Holistic Science, 2025)
Learning evaluation is an important part of the educational process because it serves to assess the achievement of learning objectives while evaluating the effectiveness of learning implementation. However, in practice, evaluation results are often only used as a basis for assigning grades without being analyzed and followed up optimally. This study aims to examine the concept of analyzing learning evaluation results and their use in learning follow-up. This study uses a library research method with a qualitative descriptive approach through a review of relevant textbooks and scientific journal articles. The results of the study indicate that the analysis of learning evaluation results plays a strategic role in identifying student learning outcomes, identifying obstacles in the learning process, and assessing the effectiveness of applied learning strategies. Through this analysis, evaluation results can be optimally utilized in the form of providing feedback, implementing remedial learning, enrichment, and continuous learning improvement to improve the quality of the learning process and outcomes.